2004
DOI: 10.1159/000079882
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pubertal Gynecomastia with the Specific Aromatase Inhibitor Anastrozole

Abstract: Gynecomastia can be detected in up to 70% of boys during puberty and in about one third of adult males. An imbalance of estrogen to androgen tissue levels is believed to be the major reason for the development of gynecomastia; as a result most medical treatments so far have tried to lower the estrogen level. Five boys with pubertal gynecomastia and breast tenderness were treated for 6 months with the selective aromatase inhibitor anastrozole. Initial plasma levels of estradiol (E2), testosterone (T)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 36 publications
0
23
0
1
Order By: Relevance
“…Tamoxifen has been successfully used as prophylaxis against the development of gynecomastia in adult patients receiving chemotherapy for prostatic cancer [14]. Although the specific aromatase inhibitor anastrozole has been advocated by some [15], recent randomized studies indicated a response similar to that achieved with placebo [12]. One of our patients received tamoxifen without improvement, and 2 additional patients were being treated by an endocrinologist for years without improvement.…”
Section: Discussionmentioning
confidence: 88%
“…Tamoxifen has been successfully used as prophylaxis against the development of gynecomastia in adult patients receiving chemotherapy for prostatic cancer [14]. Although the specific aromatase inhibitor anastrozole has been advocated by some [15], recent randomized studies indicated a response similar to that achieved with placebo [12]. One of our patients received tamoxifen without improvement, and 2 additional patients were being treated by an endocrinologist for years without improvement.…”
Section: Discussionmentioning
confidence: 88%
“…Anastrozole has been used in children with pubertal gynecomastia, 23 McCune-Albright syndrome, 24 and growth hormone deficiency. 25 In adolescent boys, treatment with anastrozole resulted in no significant changes in blood counts, urinalysis, liver profiles, or HDL and LDL concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Gynaecomastia appearing in these age ranges is considered to be physiological and it is estimated to represent approximately half of all gynaecomastia cases (5)(6)(7)(8). The presence of physiological gynaecomastia is associated with hormonal changes in various periods of life -in neonates it is associated with the presence of maternal oestrogens and in the puberty period it results from increased secretion of gonadotrophins which, in addition to testosterone synthesis, stimulate also oestrogen production and in elderly men the cause is reduced production of testosterone (5,6,7).…”
mentioning
confidence: 99%